Interaction between Ammonium Toxicity and Green Tide Development Over Seagrass Meadows: A Laboratory Study. - Francisco Moreno-Marín; Juan J Vergara; J Lucas Pérez-Llorens; Morten F Pedersen; Fernando G Brun (PLoS ONE, 2016)
Eutrophication affects seagrasses negatively by increasing light attenuation through stimulation of biomass of fast-growing, bloom-forming algae and because high concentrations of ammonium in the water can be toxic to higher plants. We hypothesized nevertheless, that moderate amounts of nitrophilic macroalgae that coexists with seagrasses under eutrophic conditions, can alleviate the harmful effects of eutrophication on seagrasses by reducing ammonium concentrations in the seawater to non-toxic levels because such algae have a very large capacity to take up inorganic nutrients. We studied therefore how combinations of different ammonium concentrations (0, 25 and 50 μM) and different standing stocks of macroalgae (i.e. 0, 1 and 6 layers of Ulva sp.) affected survival, growth and net production of the seagrass Zostera noltei. In the absence of Ulva sp., increasing ammonium concentrations had a negative influence on the performance of Z. noltei. The presence of Ulva sp. without ammonium supply had a similar, but slightly smaller, negative effect on seagrass fitness due to light attenuation. When ammonium enrichment was combined with presence of Ulva sp., Ulva sp. ameliorated some of negative effects caused by high ammonium availability although Ulva sp. lowered the availability of light. Benthic microalgae, which increased in biomass during the experiment, seemed to play a similar role as Ulva sp.--they contributed to remove ammonium from the water, and thus, aided to keep the ammonium concentrations experienced by Z. noltei at relatively non-toxic levels. Our findings show that moderate amounts of drift macroalgae, eventually combined with increasing stocks of benthic microalgae, may aid seagrasses to alleviate toxic effects of ammonium under eutrophic conditions, which highlights the importance of high functional diversity for ecosystem resistance to anthropogenic disturbance.